Magnifying inequality? Home learning environments and social reproduction during school closures in Ireland. Issue 2 (3rd April 2021) - Mohan, Gretta; Carroll, Eamonn; McCoy, Selina; Mac Domhnaill, Ciarán; Mihut, Georgiana
Abstract : COVID-19 school closures have seen the homeplace become a school-place for students and their families in Ireland. This paper presents research on the resources and supports available for students to engage with learning in their home environments. Evidence from a nationally representative survey comprising one third of second-level school leaders, conducted during the first school closures in 2020, shows that attendance and engagement appears to be influenced by the educational level of parents/guardians. The association between parental education and student engagement was stronger for Junior Certificate students but was not statistically evidenced for Leaving Certificate students. Qualitative evidence sheds further light on inequalities which characterised students' experiences of online and remote learning. Viewing these developments through a social reproduction framework, this study argues that unequal home learning environments may magnify existing inequalities. To prevent a return to the classroom with more classed outcomes, it is imperative that policy, planning and investment strive to mitigate the impact of COVID-19 on educational inequality.